Do Investors Care About Director Tenure? Insights from Executive Cognition and Social Capital Theories - Brown, Jill A.; Anderson, Anne; Salas, Jesus M.; Ward, Andrew J. (Organization Science, 2017)
Governance scholars debate the value of directors as an effective governance mechanism. We suggest that this value varies with director tenure. We study both how shareholder assessments of the value of individual directors vary with director tenure and whether director tenure actually makes a practical difference to governance effectiveness. Using data from abnormal stock price reactions to the sudden deaths of 274 outside directors, and integrating executive cognition and social capital perspectives applied to the dual roles of director monitoring and advising, our results confirm a curvilinear relationship between the assessed value of directors and tenure. We find that directors are more highly valued by investors over a tenure period between 7 and 18 years, moderated by director involvement on key committees. Further, in examining the S&P 1,500, we find that a one standard deviation increase in the percentage of outside directors in this prime tenure period strengthens the CEO pay-performance linkage by 2.5%, suggesting that directors in this tenure period are more effective in aligning CEO and shareholder interests. Our results demonstrate that individual director tenure makes a difference in governance effectiveness, and shareholders accurately assess this difference. Additionally, our findings provide important boundary conditions for when theories of executive cognition and social capital may be more/less applicable regarding director tenure.